Identification and QTL Analysis of Flavonoids and Carotenoids in Tetraploid Roses Based on an Ultra-High-Density Genetic Map - Cheng, Bixuan; Wan, Huihua; Han, Yu; Yu, Chao; Luo, Le; Pan, Huitang; Zhang, Qixiang (Frontiers in Plant Science, 2021)
Roses have high value within the flower industry. The metabolites of anthocyanins, flavonols and carotenoids in rose petals are not only responsible for the various visible petal colors, but also important bioactive compounds which are important for human health. In this study, we performed QTL analysis on pigment contents to locate major loci that determine flower color traits. A F1 population of tetraploid roses segregating for flower color was used to construct an ultra-high-density genetic linkage map by using whole genome resequencing technology to detect genome-wide SNPs. Previously developed SSR and SNP markers were also utilized to increase the marker density. Thus, a total of 9,259 markers were mapped onto seven linkage groups (LGs). The final length of the integrated map was 1285.11cM, with an average distance of 0.14 cM between adjacent markers. Anthocyanin, flavonol and carotenoid contents of the population were assayed to enable QTL analysis. Across the 33 components, 46 QTLs were detected, explaining 11.85–47.72% of phenotypic variation. The mapped QTLs were physically clustered and mainly distributed on four linkage groups, namely LG2, LG4, LG6 and LG7. These results improve the basis for flower color marker-assisted breeding of tetraploid roses and guide the development of rose products.